SEMIOTICS SYSTEM’S PERSPECTIVE IN MULTIMODAL EFL TEXTBOOK: MEANING-MAKING MODES IN FOCUS - Risma Julistiana; Anit Pranita Devi; Deni Chandra; Wida Mulyanti (Tell-us Journal)
Abstract The prominent role of textbooks as a learning media is frequently used by educators and learners alike to achieve specific learning objectives. By the standards set forth by the National Education Standards Agency (BSNP), books are deemed effective if they meet four criteria: content, presentation, language, and graphics. The elements identified in the study of multimodal discourse within semiotic systems: linguistic, visual, audio, gestural, and spatial modalities. The combination of two or more semiotic systems is defined as multimodal discourse; it facilitates learners' cognitive and creative development. This article explores the semiotic system potential by Anstey and Bull as textbook evaluation to meet the meaning-making in the EFL textbook, "English for Nusantara," published by the Ministry of Education and Culture of Indonesia. The objective of this research is to examine the concept of multimodal discourse as defined within the theoretical framework of Anstey and Bull's semiotic system theory. The design of this study was descriptive qualitative research with content analysis. The findings show that five different modes were used graded; visual 32%, gestural 23,9%, linguistics 22%, spatial 16,6%, and audio 5,4%. The textbook met the criteria for a quality educational resource, offering valuable cognitive implications for the user through its incorporation of multimodal text. It confirmed the importance of the semiotics system's potential modes in constructing meaning for both learners and educators. The meaning categorization involves: fostering the development of meaningful character traits, creating a sense of unity amidst the diversity of Pancasila, encouraging self-love, and cultivating heightened environmental awareness.